2004
DOI: 10.1175/1520-0442(2004)017<2725:iotuws>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Upper-Tropospheric Wind Shear upon Cloud Radiative Forcing in the Asian Monsoon Region

Abstract: Using the top-of-the-atmosphere radiative flux and cloud data from satellites, as well as atmospheric data from NCEP-NCAR reanalysis, this paper investigates the reason for the unusually large high-cloud amount in the Asian monsoon region during the summer monsoon season (June-September). Earlier studies attributed the large negative net cloud radiative forcing in the Asian monsoon region to the unusually large high-cloud amounts with high optical depth. Analysis during 1985-89 suggests that the unique upper-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 17 publications
3
38
0
Order By: Relevance
“…The spatial distribution of Sc clouds is also very crucial as it plays an important role in shortwave radiative forcing resulting in cooling of the surface. The confinement of Sc clouds over the Arabian Sea can be attributed to the descending motion from monsoon convection apart from lower tropospheric thermal inversion that occurs during the ISM period over this region (Sathiyamoorthy et al, 2011). The weak descending motions over the Arabian Sea during the ISM period can suppress the vertical development of clouds.…”
Section: Resultsmentioning
confidence: 99%
“…The spatial distribution of Sc clouds is also very crucial as it plays an important role in shortwave radiative forcing resulting in cooling of the surface. The confinement of Sc clouds over the Arabian Sea can be attributed to the descending motion from monsoon convection apart from lower tropospheric thermal inversion that occurs during the ISM period over this region (Sathiyamoorthy et al, 2011). The weak descending motions over the Arabian Sea during the ISM period can suppress the vertical development of clouds.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to F c , the considerably less value of F ALT observed below ∼7 km in the "pool" is most prominent in July-August. Most of the high-altitude clouds observed over the "pool" region might be cirrus clouds generated by westward spreading of outflows from the deep convective systems situated at the eastern BoB by the strong upper tropospheric easterly winds, which is a characteristic feature of ASM (e.g., Sathiyamoorthy et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Rajeevan and Srinivasan (2000) showed that the widespread coverage of a large amount of high clouds with large optical depths over the Asian summer monsoon region gives rise to a large negative net cloud-radiative forcing (NETCRF) during the June-September months. In a more recent study, Sathiyamoorthy et al (2004) pointed out that the spreading of cloud tops by the strong easterly winds in the upper troposphere can increase the high-cloud amount over the Asian monsoon region during the northern summer.…”
Section: Introductionmentioning
confidence: 99%